Some Properties For M – Homomorphism and M – Anti Homomorphism Over Q – Fuzzy M – HX Subgroups and its Level (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we define a new algebraic structure of a Q – fuzzy M – HX subgroup and the M – homomorphism and M – anti homomorphism of a Q – fuzzy M – HX subgroups. We discussed some properties characterizations of level subset of a Q – fuzzy M – HX subgroups of a M – HX group are given
Keywords: Fuzzy Set; Fuzzy Group; Q – Fuzzy Set; Q – Fuzzy Group; Q – Fuzzy M – Group; HX Group; Q – Fuzzy M – HX Group; Level Subset HX Group; M – Homomorphism; M – Anti Homomorphism.